Analisis Keterampilan Sosial Siswa pada Mata Pelajaran Ekonomi di Sekolah Menengah Atas Negeri 2 Kampar - Nurshahni Rizki Abdaniati; Rohani Rohani (Lembaga Anotero Scientific, 2020)
This research aimed at knowing student social skills on Economics subject at State Senior High School 2 Kampar. It was instigated by students who did not appreciate their friend opinions, who were not confident, and who could not adjust themselves to their friends and environments. It was a qualitative descriptive research. The subjects of this research were the students, and the object was student social skill on Economics subject at State Senior High School 2 Kampar. The informants were 216 students. Purposive sampling technique was used in this research, so 7 students were selected as the key informants, and the additional informants were Economics subject teachers. Observation, interview, and documentation were the techniques of collecting the data. The technique of analyzing the data was qualitative descriptive. Based on the research findings, the percentage of student social skill on Economics subject at State Senior High School 2 Kampar was 44.67%. The analysis results showed that the ability indicators of empathy, communication, social interaction, controlling aggression, open attitude, helping behavior, understanding his/herself, learning behavior were on good enough category that was on the range score of 41%-60%. It meant that by analyzing some indicators of social skills overall students were good enough in adjusting themselves to their friends and environments, students also could cooperate well, and they were able to show their self-confidence.